HUBUNGAN PENGETAHUAN TENAGA KESEHATAN TENTANG ASI EKSKLUSIF DENGAN KEMAMPUAN MEMBERIKAN PENDIDIKAN KESEHATAN ASI EKSKLUSIF PADA IBU PRENATAL DI PUSKESMAS II KARTASURA - Setyowati, Eksi; Rahayuningsih, Faizah Bety (Jurnal Berita Ilmu Keperawatan, 2008)
There is a low understanding of prenatal mother about the important of giving exclusive breast feeding, because medical education given by officers is all about the outline. It can be said that there is less scope in doing medical education. This research is to know the relation of medical officers about exclusive breast feeding and ability of giving education about exclusive breast feeding to prenatal mother on Puskesmas II Kartasura.It is descriptive research with quantitative research in order to give description about circumstance. Research place is on Puskesmas II Kartasura by taking 18 medical officers as samples work in Kid and Mother Medical Room. Method of collecting data is using questionnaire prime method. It is gain data of officer’s ability. Data collected then analyzed by using Kendall tau correlation. Result of the study shows that : (1) The level of medical officer’s understanding about exclusive breast feeding on Puskesmas II Kartasura is good (44,4%), so it is able to give medical education to prenatal mothers. (2) The ability of medical officers in giving medical education about exclusive breast feeding on Puskesmas II Kartasura is good (83,3%). (3) There is a positive and significant correlation between level officers understanding with understanding ability about exclusive breast feeding to prenatal mother on Puskesmas II Kartasura. This is proven from the analysis result of Kendall tau correlation (0,585), which is accepted on significant level 5%